2020
DOI: 10.1111/vco.12599
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional diets and nutritional supplements are more common in dogs with cancer compared to healthy dogs: An online global survey of 345 dog owners

Abstract: This survey aimed to investigate and compare diet type and supplement use between dogs (Canis lupus familiaris, L.) with cancer and a population of owner-reported healthy dogs and to assess the sources of information dog owners consult. Respondents were mainly from English-speaking countries. Dogs were considered healthy (N = 213) if owners reported them to be in good health. Dogs were included in the cancer group (N = 132) if the owner reported that their dog had been diagnosed with cancer. An online survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…Mushroom-based and CBD/THC supplements were added at the highest rates after a cancer diagnosis; this is consistent with these supplements being more commonly given to dogs with cancer when compared to healthy dogs. 11 This helps to confirm that some of these differences are attributable to a cancer diagnosis, rather than solely because of other factors such as age. Although mushrooms have anticancer potential in mice, 19,20 this has not been shown in dogs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Mushroom-based and CBD/THC supplements were added at the highest rates after a cancer diagnosis; this is consistent with these supplements being more commonly given to dogs with cancer when compared to healthy dogs. 11 This helps to confirm that some of these differences are attributable to a cancer diagnosis, rather than solely because of other factors such as age. Although mushrooms have anticancer potential in mice, 19,20 this has not been shown in dogs.…”
Section: Discussionmentioning
confidence: 92%
“…12 For total number of dogs receiving supplements, our data showed no significant change after a cancer diagnosis. Dogs with cancer are more likely to receive supplements than healthy dogs in the general population, 11 which was not evaluated in this study. Our findings might also reflect the owner's focus on supporting their dog during chemotherapy and other treatments during the period of time close to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, self-report owner surveys have been used in both veterinary and behaviour-problem contexts to investigate potential predictors of clinical or behaviour-problem morbidity, as well as highlighting broader welfare concerns associated with poor husbandry practices amongst some owners. For example, a number of studies have considered owner reports of diet and behaviour management in relation to dog obesity [15][16][17] while Oxley et al (2019) investigated the ways in which owners (and other caregivers) reported handling their pet rabbits 18 , a feature of husbandry with known importance for rabbit welfare. Pet owner surveys clearly have a role to play in informing health, husbandry and welfare improvements for domesticated species.…”
Section: Introductionmentioning
confidence: 99%
“…OVER the past few years, numerous nutraceutical products with claimed ‘anticancer’ properties, such as chondroprotective agents, turmeric, curcumin, mushroom extracts and various immune support medications, have been available on the market, and a recent survey highlighted that there has been a rise in their use by owners of dogs with cancer 1 . However, there is limited to no evidence on the safety or effectiveness of these products, and also no indication about any possible interaction with chemotherapy drugs, and so we argue that their use should be discouraged.…”
mentioning
confidence: 99%